Aggregation and Dissolution Kinetics of Nanosilver in Seawater - Feng Chen, Shao; Zhang, Hongyin (Asian Journal of Chemistry, 2012)
This study shows the synthesis of citrate capped nanosilver using Tollens method and the effect of seawater on its physcochemical properties. The results show that the average particle size of nanosilver is 66 nm in deionized water condition and 1800 nm in seawater condition. x-Potentials of nanosilver in deionized water is more negative than that in seawater. This study also indicates that aggregation rate of nanosilver in seawater is higher than that in deionized water. At last, more dissolution of nanosilver was measured in deionized water than that in seawater.